Physiopathological implications of genetic variability in the complement alternative pathway - Rodríguez de Córdoba, Santiago (Henry Stewart Talks, 2018)
Inherited complement-related diseases, Complement genetic variability, Genotype-phenotype correlations, Complement dysregulation in age-related macular degeneration (AMD), The complotype, Complex rearrangements of complement genes, Complement genetic testing